TREATMENT METHODS FOR EARLY CHILDHOOD ANISOMETROPIC MYOPIA AND PREVENTION OF AMBLYOPIA - Bakhronov Dilshodbek Jamshid o‘g‘li (Western European Studies, 2025)
Anisometropic myopia in early childhood represents a significant clinical concern due to its potential to disrupt normal visual development and cause amblyopia. Anisometropia, which is the presence of a significant difference in refractive error between the two eyes, can compromise the brain’s ability to fuse images from both eyes into a single, clear vision. When this condition develops alongside myopia in one eye during the critical periods of childhood, there is a heightened risk that amblyopia may develop if timely and effective intervention is not administered
Keywords: anisometropic myopia; early childhood; amblyopia prevention; cycloplegic retinoscopy